Assessing the validity of recent estimates of problematic drug use in England. Issue 1 (18th September 2008) - Frisher, M; Forsyth, A
Abstract : Background: The Home Office has recently published estimates which, for the first time, provide a "robust national estimate" of the number of problematic drug users in England. The 2004/05 and 2005/06 estimates are the highest estimates ever produced for England and coincide with the highest ever government annual expenditure on combating illicit drug use. Methods and Results: Review of a range of data sources that indicate a downward trend in problematic drug use in recent years. Conclusions: The validity of the estimates is important for drug policy, and the paper considers the implications of both increasing and decreasing levels of problematic drug use.